Pendampingan Matrikulasi Kompetensi Bahasa Arab Berbasis Pendekatan Asset Based Community Development (ABCD) - Syarifah, Ainun; Jannah, Ida Miftakhul; Sholehan, Sholehan (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2023)
Purpose- This research aims to describe the process of assisting the matriculation of Arabic competence at Madrasah Aliyah Negeri (MAN) 1 Pasuruan. Design/Methodology/Approach- This research was conducted to add to the treasures of community assistance with the Asset Based Community Development (ABCD) approach. The method used in this mentoring process uses the Asset Based Community Development (ABCD) approach with a five-step method, namely Discovery, Dream, Design, Define, Destiny. qualitative data collection is done by observation, interviews and documentation. Sources of data are teachers and students as well as assistants. While the collected data is processed and analyzed using data reduction flow, data display and conclusion drawing. Findings- The results of the assistance show that the Arabic language competency matriculation assistance at MAN 1 Pasuruan was carried out in five stages, namely Discovery, Dream, Design, Define, Destiny. Every stage of this assistance is carried out properly. While the results of this assistance are also very good, where students are able to explore the competencies they have and all of them follow the process of this activity properly. So that they are able to take part in Arabic language competitions both held by local madrasas and on a wider scale.  Research Limitations/Implications- This research is limited to facilitation of Arabic competency matriculation at MAN 1 Pasuruan. This matriculation assistance focuses on efforts to increase the competency of students in mastering Arabic language skills which are focused on preparation for participating in various Arabic language competitions.